Chinese Tertiary-Level English as a Foreign Language Teachers’ Emotional Experience and Expression in Relation to Teacher-Student Interaction - Xie, Xinfeng; Jiang, Guiying (Frontiers in Psychology, 2021)
The paper examines the emotional experience and expression of Chinese tertiary-level English as foreign language (EFL) teachers and their interaction with their students. Data were drawn from semi-structured in-depth interviews with 10 EFL teachers recruited from 7 universities of different levels in China and were analyzed in light of Emotional Geography Theory. The results reveal that Chinese tertiary-level EFL teachers experience more negative emotions than positive ones. The emotions most frequently reported by them are anger, enjoyment, anxiety, disappointment, and ambivalence. When it comes to emotional expressions, Chinese tertiary-level EFL teachers tend to display positive emotions by following the emotional rules of school settings. This study also uncovers that EFL teaching in Chinese universities is characterized by EFL teachers’ physical and moral distance from but political closeness to students, all of which are the sources of EFL teachers’ negative emotions. The need for providing positive psychology intervention for EFL teachers is then suggested.